The Relationship Between Demographic Characteristics and Knowledge with Preventive Behaviors of Hypertension Complications Among the Community in the Jatiranggon Community Health Center - Arindya, Sekar Ayu Putri; Astrid, Maria (Celebes Nursing Journal, 2025)
Introduction: Hypertension is defined as a persistent increase in blood pressure which, if not controlled, can lead to complications such as stroke, heart attack, heart failure, kidney damage, retinopathy, and even death. Objectives: This study aimed to examine the relationship between demographic characteristics and knowledge with hypertension complication prevention behaviors in the Jatiranggon Community Health Center service area. Methods: This quantitative correlational study with a cross-sectional design involved 105 respondents aged 18–59 years, selected using purposive sampling based on predetermined inclusion criteria. Data were collected using structured questionnaires and analyzed with Chi-square, Kendall’s tau-c, and Kendall’s tau-b tests. Results: Most respondents were aged 56–65 years (42.9%), female (53.3%), had secondary education (60.0%), had Stage 1 hypertension (53.3%), and demonstrated good knowledge (90.5%). However, 68.6% exhibited only fair preventive behaviors. Bivariate analysis showed a significant association between gender and preventive behaviors (p < 0.05), with females more likely to engage in such behaviors. No significant associations were found for age, educational level, blood pressure status, or knowledge. Conclusion: Gender demonstrated a significant association with hypertension complication prevention behaviors, while age, education, blood pressure, and knowledge did not show significant relationships.